[Acute pancreatitis--a protocol for diagnosis and treatment] - Berger, P; Mollema, R; Girbes, A; van Dullemen, H; Bosscha, K; Gooszen, H; Ploeg, R (2001)
Acute pancreatitis remains a disease with high morbidity and mortality. Acute pancreatitis can be subdivided in acute interstitial pancreatitis and necrotising pancreatitis, largely compatible with clinically mild and severe pancreatitis. This diagnosis is made on the basis of patient history, physical examination, laboratory parameters, contrast CT scan and, occasionally, endoscopic retrograde cholangiopancreatography. Prognosis on admission can be established using a scoring system such as the modified Glasgow score, the Ranson score and the 'Acute physiology and chronic health evaluation'--(APACHE)-II-score. The treatment of acute pancreatitis is primarily conservative. Indications for surgical intervention are: progressive sepsis despite maximum conservative management, an established infection of (peri)pancreatic necrosis, peripancreatic abscess and perforation of stomach, small intestine or colon. The purpose of an operation is to remove necrotic tissue, achieve adequate drainage of the necrotic area or to treat a perforation. The Groningen and Utrecht University Hospitals have collaborated to develop a protocol to standardise the diagnostic approach, management, timing and choice of surgical intervention, as well as to prospectively investigate the effect of such a strategy in patients with acute pancreatitis.